2013
DOI: 10.2172/1095950
|View full text |Cite
|
Sign up to set email alerts
|

Formulating a simplified equivalent representation of distribution circuits for PV impact studies.

Abstract: With an increasing number of Distributed Generation (DG) being connected on the distribution system, a method for simplifying the complexity of the distribution system to an equivalent representation of the feeder is advantageous for streamlining the interconnection study process. The general characteristics of the system can be retained while reducing the modeling effort required. This report presents a method of simplifying feeders to only specified buses-ofinterest. These buses-of-interest can be potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In spite of the error, methods using this assumption have shown to provide higher accuracy than other leading methods [24][25][26]. Further, the results provided in [27] demonstrate that the load type selected has minor effects on the simulation results.…”
Section: Analytical Approach a Assumptionsmentioning
confidence: 94%
“…In spite of the error, methods using this assumption have shown to provide higher accuracy than other leading methods [24][25][26]. Further, the results provided in [27] demonstrate that the load type selected has minor effects on the simulation results.…”
Section: Analytical Approach a Assumptionsmentioning
confidence: 94%
“…It also allows the user to select which buses should remain in the final circuit. Technical losses are not preserved though [7]. The same disadvantages pointed out in [4] applies here as well.…”
Section: Introductionmentioning
confidence: 53%
“…Additionally, it is shown that the TL are preserved after the reduction technique for the two selected feeders. Nevertheless, this conclusion cannot be generalized since it is mathematically shown in [7] that the method philosophy does not assure TL equivalence. Unfortunately, neither [6]- [8] evaluated the TL errors in their investigations.…”
Section: Resultsmentioning
confidence: 99%
“…This clustering validation could also be used to estimate the level of error introduced by clustering rather than modeling all feeders. In many cases, computational demands can be reduced further by using simplified equivalent distribution networks with aggregated loads (Reno et al 2013;Baggu et al 2014).…”
Section: Estimating Distribution Losses Via Power Flow Modelingmentioning
confidence: 99%